Air-sea CO2 exchange rate in the northern Indian Ocean based on coral radiocarbon records. (February 2022) - Raj, Harsh; Bhushan, Ravi; Banerji, Upasana S.; Muruganantham, M.; Shah, Chinmay; Nambiar, Romi; Dabhi, Ankur J.
Abstract: Corals growing in shallow oceanic regions record the radiocarbon variations in ocean surface waters. Tracing bomb radiocarbon in various carbon reservoirs, can help understand the pathways and rates of carbon exchange between the different reservoirs. The northern Indian Ocean comprising two adjoining basins the Arabian Sea and the Bay of Bengal demonstrates contrasting behaviour both in its hydrological condition and CO2 sequestration. In this study, coral based bomb radiocarbon records from the Lakshadweep Islands and the Andaman Islands in the northern Indian Ocean have been analysed. The estimates of air-sea CO2 exchange rate based on bomb radiocarbon for the Lakshadweep is 13.4 ± 2.1 mol m −2 yr −1 and for the northern Andaman is 8.8 ± 1.3 mol m −2 yr −1 . The bomb radiocarbon based air-sea CO2 exchange over the Indian Ocean follow the trend of empirical relationship with wind speed. Using the air-sea CO2 exchange rates, the net regional CO2 fluxes over the Lakshadweep and the northern Andaman region has been determined. Highlights: Post bomb radiocarbon in the northern Andaman region show relatively enriched values compared to the Lakshadweep region. Estimated air-sea CO2 exchange rate over Lakshadweep region is 13.4 ± 2.1 mol m −2 yr −1 and over northern Andaman region is 8.8 ± 1.3 mol m −2 yr −1 . The Lakshadweep and the northern Andaman region show net CO2 flux of 2.5 and −0.3 Tg C yr −1 respectively.